Analyzing biological and molecular characteristics and genomic damage induced by exposure to asbestos (2019)
Asbestos is one of the most important occupational carcinogens. Currently, about 125 million people worldwide are exposed to asbestos in the workplace. According to global estimates, at least 107,000 people die each year from lung cancer, mesothelioma, and asbestosis as a result of occupational exposure to asbestos. The high pathogenicity of this material is currently known, being associated with the development of pulmonary diseases, of which lung cancer is the main cause of death due to exposure to this mineral. Pulmonary diseases related to asbestos are a common clinical problem and a major health concern worldwide. Extensive research has identified many important pathogenic mechanisms; however, the precise molecular mechanisms involved, and the generated genomic damage that lead to the development of these diseases, are not completely understood. The modes of action that underlie this type of disease seem to differ depending on the type of fiber, lung clearance, and genetics. This evidences the need to increase our knowledge about these effects on human health. This review focuses on the characteristics of asbestos and the cellular and genomic damage generated in humans via exposure. © 2019 Zhang et al.